2008
DOI: 10.2319/112006-468.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Screening and Treatment of Root Resorption in Orthodontic Practices in Greece and Sweden

Abstract: Objective: To evaluate the perception of Greek and Swedish orthodontic practitioners regarding the possible occurrence and prognosis of root resorption occurring during orthodontic treatment and to estimate practitioners' approaches to the diagnosis of preexisting root resorption, screening of prevalence, and treatment planning approach when moderate or severe root resorption is present. Materials and Methods: Questionnaires were received from randomly selected Greek (n ϭ 90) and Swedish (n ϭ 106) practitioner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…24 Usually, two-dimensional radiographic (2D) methods as periapical or panoramic radiographs are obtained before, during, and after orthodontic treatment to record OIRR. 25 Studies using 2D imaging techniques revealed OIRR to be less than 0.60 mm at the end of treatment. 26 However, OIRR affects all aspect of the root surface in 3D therefore, 2D radiographs might mask the true degree of OIRR.…”
Section: Discussionmentioning
confidence: 98%
“…24 Usually, two-dimensional radiographic (2D) methods as periapical or panoramic radiographs are obtained before, during, and after orthodontic treatment to record OIRR. 25 Studies using 2D imaging techniques revealed OIRR to be less than 0.60 mm at the end of treatment. 26 However, OIRR affects all aspect of the root surface in 3D therefore, 2D radiographs might mask the true degree of OIRR.…”
Section: Discussionmentioning
confidence: 98%
“…It has been established that the management of OIIRR related to OTM does not have definitive guidelines and there are global differences and similarities in clinical approaches 138,139 . There appears to be similar confusion amongst clinicians concerning the orthodontic management of traumatized teeth 140–143 .…”
Section: Orthodontics and Traumatized Teethmentioning
confidence: 99%
“…It has been established that the management of OIIRR related to OTM does not have definitive guidelines and there are global differences and similarities in clinical approaches. 138,139 There appears to be similar confusion amongst clinicians concerning the orthodontic management of traumatized teeth. [140][141][142][143] Previous recommendations have been published concerning waiting periods prior to OTM for traumatized teeth, [56][57][58]144,145 but these were often based on the same literature.…”
Section: Clinical Guidelines and Recommendationsmentioning
confidence: 99%
“…Clinical examination is not reliable as clinical symptoms are almost absent, and increased tooth mobility is seen only in extremely severe cases with additional alveolar bone loss resulting through time (Jönsson et al, 2007). Moreover, EARR is being monitored before, during, and after orthodontic treatment usually by using two-dimensional radiographic (2D) methods like periapical or panoramic radiographs (OPT) (Makedonas and Hansen, 2008). However, apical root resorption occurring after orthodontic tooth movement is usually underestimated when evaluated on panoramic radiographs (Dudic et al, 2009) (Picture 4.7.5.1).…”
Section: Diagnosis Of Earrmentioning
confidence: 99%